Thermal Conductivity of Dry Sands Treated with Microbial-Induced Calcium Carbonate Precipitation. (3rd February 2019) - Wang, Zhaoyu; Zhang, Nan; Lin, Fei; Ding, Jinhua; Yang, Huimin
Abstract : With an increasing energy demand, exploration and utilization of new energy resources become more significant recently. Geothermal energy, characterized as a clean, renewable, and sustainable energy, has various engineering applications. Microbial-induced calcium carbonate precipitation (MICP) technique has a potential to improve soil thermal properties for geothermal applications. In this study, thermal conductivity of dry sands treated using MICP technique with different treatment cycles was investigated in laboratory. The results showed that thermal conductivity of MICP-treated sands was much higher than that of the untreated sand under dry condition and it increased with increasing treatment cycles. Based on the scanning electron microscopy (SEM) analyses, it is found MICP-induced CaCO3 crystals are being formed among sand particles functioned as "thermal bridge, " which provided more highly effective heat transfer path. It is concluded that the MICP technique could significantly improve the thermal conductivity of sands and the overall heat transfer efficiency. It is advantageous to use MICP-treated soils as enhanced grout materials for underground energy geostructures.